Spontaneous Cervical Artery Dissection: The Borgess Classification - Al-Ali, Firas; Perry, Brandon C. (Frontiers in Neurology, 2013)
ABSTRACT Background and Purpose: The pathogenesis of spontaneous cervical artery dissections (sCAD) and its best medical treatment are debated. This may be due to a lack of clear classification of sCAD. We propose the new Borgess classification of sCAD, based on the presence or absence of intimal tear as depicted on imaging studies and effect on blood flow. Materials and Methods: This is a single-center investigator-initiated registry on consecutive patients treated for sCAD. In the Borgess classification, type I dissections have intact intima and type II dissections have an intimal tear. Results: Forty-four patients and 52 dissected arteries were found. Forty-nine of 52 dissections (93%) were treated with dual anti-platelet therapy. Twenty-one of 52 dissections were type I; 31 were type II. Type I dissections were more likely to present with ischemic symptoms (stroke, TIA) (p=0.001). More type I dissections occurred in the vertebral artery, while more type II dissections occurred in the internal carotid artery (p